Grand Union between Tibet and Mongolia: Unfulfilled Dream of the 13th Dalai Lama - Tsedenbamba Batbayar (The Mongolian Journal of International Affairs, 2013)
Since the late sixteenth century when Altan Khan of Tumed in Southern Mongolia adopted the Yellow Hat sect of Tibetan Buddhism and supported it as the common faith of the Mongol people, the teaching and discipline of Buddhism greatly influenced the customs, society, and various activities of the nomadic Mongols. The Mongolian version of Tibetan Buddhism was called Lamaism, and the Buddhist monks were known as lamas.